2022
DOI: 10.1111/jnc.15678
|View full text |Cite
|
Sign up to set email alerts
|

STING mediates neuroinflammatory response by activating NLRP3‐related pyroptosis in severe traumatic brain injury

Abstract: Long‐term neurological deficits after severe traumatic brain injury (TBI), including cognitive dysfunction and emotional impairments, can significantly impair rehabilitation. Glial activation induced by inflammatory response is involved in the neurological deficits post‐TBI. This study aimed to investigate the role of the stimulator of interferon genes (STING)–nucleotide‐binding oligomerization domain‐like receptor pyrin domain‐containing‐3 (NLRP3) signaling in a rodent model of severe TBI. Severe TBI models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 80 publications
3
21
0
Order By: Relevance
“…Previous studies have demonstrated that the cGAS-STING pathway is a major cytosolic DNA sensor and plays a vital role in the microglial activity and neuroin ammatory responses after TBI [29,43,44]. Consistently, our results showed that TBI led to the upregulation of STING, activation of TBK1 and IRF3, and induction of STING-associated IFN-β and IL-6.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies have demonstrated that the cGAS-STING pathway is a major cytosolic DNA sensor and plays a vital role in the microglial activity and neuroin ammatory responses after TBI [29,43,44]. Consistently, our results showed that TBI led to the upregulation of STING, activation of TBK1 and IRF3, and induction of STING-associated IFN-β and IL-6.…”
Section: Discussionsupporting
confidence: 90%
“…The STING antagonist C-176 (S6575, Selleck, USA) was dissolved in a stock solution containing 5% dimethyl sulfoxide (DMSO) and 95% corn oil and then diluted in saline (5% v/v). As reported previously [29], 10 mg/kg C-176 or vehicle (saline containing 5% stock solution) was administered i.p. 1 h after TBI and then every day until the mice were killed.…”
Section: Stimulators Of Interferon Genes (Sting) Antagonist Administr...mentioning
confidence: 99%
“…The STING antagonist C-176 (S6575, Selleck, USA) was dissolved in a stock solution containing 5% dimethyl sulfoxide (DMSO) and 95% corn oil and then diluted in saline (5% v/v). As previously reported ( 29 ), 10 mg/kg C-176 or an equal volume of vehicle (saline containing 5% stock solution) was administered i.p. 1 h after TBI and once per day for three consecutive days.…”
Section: Methodsmentioning
confidence: 99%
“…Recently studies have revealed that STING not only provokes the TBK1/IRF3/IFNs pathway in a classical way but also is involved in the activation of ER stress and unfolded protein response (UPR) ( 25 27 ). STING has been reported to play an important role in regulating the neuroinflammatory process and pyroptosis after TBI ( 28 , 29 ), but its effects on NLRP1 inflammasome-mediated neuronal cell death have not been explored in TBI. Interestingly, Inositol-requiring enzyme-1 alpha (IRE1α), one of the sensor proteins in the endoplasmic reticulum associated with ER stress, has been shown to regulate NLRP1-mediated neuronal pyroptosis in a neonatal hypoxic-ischemic encephalopathy rat model ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many neuroin ammatory diseases, such as ischemic injury, subarachnoid hemorrhage (SAH), traumatic brain injury (TBI), Alzheimer's disease (AD), and PD are characterized by overactivation of the cGAS-STING pathway and expression of type I interferon (IFN) and in ammatory cytokines which underscore pathological progression [6][7][8][9][10][11]. Thus, STING has been recognized as a critical and promising therapeutic target for various neuroin ammatory diseases.…”
Section: Introductionmentioning
confidence: 99%